SnxMoyS2 / SnS2 heterojunction with adjustable 1T metal phase proportion and preparation method of SnxMoyS2 / SnS2 heterojunction

Through liquid phase growth technology and sodium chloride salt adjustment of NaCl, SnxMoyS2/SnS2 heterojunctions with different 1T metal ratios were prepared, which solved the problem of difficult regulating the 1T content in TMDCs materials, and achieved high sensitivity and low noise gas sensing effect.

CN119750649APending Publication Date: 2025-04-04SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411951924.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the field of gas sensing, the content of metal phase 1T is difficult to effectively regulate, resulting in noise level and sensitivity problems of the sensor.

Method used

Through liquid phase growth technology and sodium chloride salt, the addition ratio of NaCl is adjusted, so that SnO2 in SnO2/MoO3 forms medium tin oxychloride, promote the transformation of 2H-MoS2 to 1T-MoS2, and prepare SnxMoyS2/SnS2 heterojunctions with different 1T metal ratios.

Benefits of technology

The adjustable proportion of 1T metal is realized, which reduces the contact resistance, improves the carrier mobility at the interface, and improves the sensitivity and efficiency of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750649A_ABST
    Figure CN119750649A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heterostructure preparation, in particular to a SnxMoyS2 / SnS2 heterojunction with an adjustable 1T metal phase proportion and a preparation method of the SnxMoyS2 / SnS2 heterojunction, and the preparation method comprises the following steps: taking molybdate and tetravalent tin salt as raw materials, taking water as a solvent, and carrying out hydrothermal synthesis to obtain SnO2 / MoO3 nanorods; the invention relates to a preparation method of SnxMoyS2 / SnS2 heterojunction, SnS2 nanosheets are used as a template and mixed with SnO2 / MoO3 nanorods and CS (NH2) 2 to obtain a mixed solution, polyvinylpyrrolidone and NaCl are added into the mixed solution to generate turbid liquid, the turbid liquid is subjected to a hydrothermal reaction to obtain the SnxMoyS2 / SnS2 heterojunction, the preparation method provides mild reaction conditions and accurate control over the material growth process, regulation and control of a metal phase are easy to achieve, and the SnxMoyS2 / SnS2 heterojunction is prepared. By regulating and controlling the metal phase proportion, excellent electronic transmission performance can be realized, and the efficiency and the performance of an electronic device can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heterostructure preparation, and in particular to a Sn- x Mo y S2 / SnS2 heterojunction and preparation method thereof. Background Art

[0002] In recent years, layered transition metal sulfides (TMDCs) have attracted extensive attention in the field of gas sensing due to their excellent electrical properties. It is well known that the layers of TMDCs materials are connected by weak van der Waals forces. When metal atoms such as Ag, Au, Co, Cu, Fe, In, Ni and Sn are inserted between the layers, TMDCs change from semiconductor properties to metallic properties. This change in crystal structure affects its electrical properties and thus changes the sensitivity of the sensor. When the content of the metal phase 1T is too high, the noise level of the sensor can be effectively reduced, but it will also cause its response signal to the gas to become weaker, affecting the sensitivity of the sensor. On the contrary, when the content of the metal phase 1T is too low, the noise of the sensor will increase significantly, making it unable to distinguish the response signal of low-concentration gas.

[0003] Therefore, regulating the appropriate ratio of the metal phase 1T and the semiconductor phase 2H in TMDCs materials is crucial to reduce the detection line and improve the sensitivity of the sensor. Although existing literature has revealed the transformation of semiconductor 2H-MoS2 to metallic 1T-MoS2, existing methods cannot effectively regulate the 1T / 2H ratio of MoS2. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention aims to provide a Sn2O3 nanostructured ... x Mo y S2 / SnS2 heterojunction and preparation method thereof, the present invention utilizes liquid phase growth technology and sodium chloride salt, and adjusts the addition ratio of NaCl to make SnO2 in SnO2 / MoO3 form medium oxychloride SnO z Cl q , the salt can reduce the melting point of the reactants and promote the formation of intermediates, thereby promoting the metal chalcogenide Sn x Mo y The crystal formation of S2 makes 2H-MoS2 transform to 1T-MoS2, and Sn with different degrees of 1T is prepared. x Mo y The S2 / SnS2 heterojunction, the preparation method of the present invention has the advantages of environmental protection, low cost, good controllability and high efficiency.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A Sn x Mo y The method for preparing a S2 / SnS2 heterojunction comprises the following steps:

[0007] SnO2 / MoO3 nanorod transition product is obtained by hydrothermal synthesis using molybdate and tetravalent tin salt as raw materials and water as solvent.

[0008] SnS2 nanosheets are used as templates, mixed with SnO2 / MoO3 nanorod transition products and CS(NH2)2 for sulfurization reaction to obtain a mixed solution, polyvinyl pyrrolidone template and NaCl are added to the mixed solution to generate a suspension, and the suspension is subjected to a hydrothermal reaction. During the hydrothermal reaction, NaCl causes SnO2 in SnO2 / MoO3 to form tin oxide chloride, which then reacts with MoO3 in SnO2 / MoO3 and S in SnS2 nanosheets to transform 2H-MoS2 into 1T-MoS2. By adjusting the amount of NaCl added, Sn with different 1T metal phase ratios can be obtained. x Mo y S2 / SnS2 heterojunction.

[0009] The invention uses molybdate and tetravalent tin salt as raw materials, obtains SnO2 / MoO3 nanorod transition product through hydrothermal synthesis, then uses SnS2 nanosheet as template, mixes with SnO2 / MoO3 nanorod transition product and CS(NH2)2 for sulfidation reaction, obtains mixed solution, adds polyvinyl pyrrolidone template and NaCl to the mixed solution, generates suspension solution, and finally performs hydrothermal reaction on the suspension solution, wherein NaCl makes SnO2 in SnO2 / MoO3 form medium oxychloride, and the medium oxychloride reacts with MoO3 in SnO2 / MoO3 and S in SnS2 nanosheet to obtain Sn x Mo y S2 / SnS2 heterojunction, Sn x Mo y The heterogeneous heteroatom Sn is used for doping in the S2 / SnS2 heterojunction, and the SnO2 in SnO2 / MoO3 is formed into tin oxychloride SnO by adjusting the addition ratio of NaCl. z Cl q , the salt can reduce the melting point of the reactants and promote the formation of intermediates, thereby promoting the metal chalcogenide Sn x Mo y Crystal formation of S2, thus obtaining Sn with different 1T ratios x Mo y S2 / SnS2, achieving low contact resistance and improving carrier mobility at the interface.

[0010] In a preferred embodiment of the present invention, the molar ratio of NaCl to the tetravalent tin salt is 0.5-1.5:1.

[0011] In a preferred embodiment of the present invention, the molar ratio of molybdate to tetravalent tin salt is 1:0.1-0.45, and the usage ratio of tetravalent tin salt to water is 0.1 mol-0.45 mol:19 mL-20 mL.

[0012] In a preferred embodiment of the present invention, the mass ratio of SnS2 nanosheets to SnO2 / MoO3 nanorod transition product is 5:0.5-1, and the mass ratio of SnO2 / MoO3 nanorods to CS(NH2)2 is 1:30-33.

[0013] In a preferred embodiment of the present invention, the hydrothermal reaction temperature for preparing the SnO2 / MoO3 nanorod transition product is 180°C to 220°C, and the hydrothermal reaction time is 10h to 12h.

[0014] In a preferred embodiment of the present invention, Sn is prepared x Mo y In the case of S2 / SnS2 heterojunction, the hydrothermal reaction temperature is 180°C to 220°C, and the hydrothermal reaction time is 28h to 30h.

[0015] In a preferred embodiment of the present invention, the molybdate is ammonium molybdate or sodium molybdate dihydrate.

[0016] In a preferred embodiment of the present invention, the SnS2 nanosheets are prepared by the following steps:

[0017] Using thiourea as a sulfur source and tetravalent tin salt as a tin source and water as a solvent, a hydrothermal reaction is carried out at 160°C to 260°C for 10h to 12h to obtain SnS2 nanosheets.

[0018] In a preferred embodiment of the present invention, the usage ratio of thiourea, tetravalent tin salt and water is 15 mol: 1 mol: 19 mL to 20 mL.

[0019] Another object of the present invention is to provide a SnN with a controllable 1T metal phase ratio obtained by any of the above-mentioned preparation methods. x Mo y S2 / SnS2 heterojunction.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention uses molybdate and tetravalent tin salt as raw materials, obtains SnO2 / MoO3 nanorod transition product through hydrothermal synthesis, then uses SnS2 nanosheet as template, mixes with SnO2 / MoO3 nanorod transition product and CS(NH2)2 for sulfidation reaction, obtains a mixed solution, adds polyvinyl pyrrolidone template and NaCl to the mixed solution, generates a suspension, and finally performs hydrothermal reaction on the suspension, wherein NaCl causes SnO2 in SnO2 / MoO3 to form tin oxide chloride, which then reacts with MoO3 in SnO2 / MoO3 and S in SnS2 nanosheet to obtain Sn x Mo y S2 / SnS2 heterojunction, Sn x Mo y The heterogeneous heteroatom Sn is used for doping in the S2 / SnS2 heterojunction, and the SnO2 in SnO2 / MoO3 is formed into tin oxychloride SnO by adjusting the addition ratio of NaCl. z Cl q , the salt can reduce the melting point of the reactants and promote the formation of intermediates, thereby promoting the metal chalcogenide Sn x Mo y The crystal formation of S2 causes the transformation of 2H-MoS2 to 1T-MoS2, thus obtaining Sn with different 1T ratios. x Mo y S2 / SnS2, achieving low contact resistance and improving carrier mobility at the interface.

[0022] 2. The preparation method of the present invention provides mild reaction conditions and precise control over the material growth process, making it easy to regulate the metal phase. By regulating the metal phase ratio, superior electron transport performance can be achieved, which helps to improve the efficiency and performance of electronic devices.

[0023] 3. The present invention uses liquid phase growth technology and sodium chloride salt to prepare Sn with different 1T levels x Mo y S2 / SnS2 heterostructure, this method has the advantages of environmental protection, low cost, good controllability and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 a) SEM and b) XRD patterns of SnO2 / MoO3 nanorods prepared in Example 1 of the present invention.

[0025] Figure 2 SnS2 prepared in Examples 1 to 4 of the present invention and SnS with different NaCl contents x Mo y SEM images of S2 / SnS2; a) SnS2; b) Sn x Moy S2 / SnS2; c) Sn prepared in Example 1 x Mo y S2 / SnS2; d) Sn prepared in Example 2 x Mo y S2 / SnS2; e) Sn prepared in Example 3 x MoyS2 / SnS2; f) Sn prepared in Example 4 x Mo y S2 / SnS2.

[0026] Figure 3 Sn prepared in Example 1 of the present invention x Mo y TEM image of S2 / SnS2; a) TEM; b) high resolution image.

[0027] Figure 4 This is the XRD pattern of SnS2 prepared in Example 1 of the present invention.

[0028] Figure 5 a) is Sn with different NaCl contents prepared in Examples 1 to 4 x Mo y XRD diagram of S2 / SnS2, b) Sn prepared in Example 1 x Mo y Raman map of S2 / SnS2.

[0029] Figure 6 Sn with different NaCl contents prepared in Examples 1 to 4 of the present invention x Mo y XPS graph of molybdenum element and corresponding 1T content of S2 / SnS2; a) Sn x Mo y S2 / SnS2; b) Sn prepared in Example 1 x Mo y S2 / SnS2; c) Sn prepared in Example 2 x Mo y S2 / SnS2; d) Sn prepared in Example 3 x Mo y S2 / SnS2; e) Sn prepared in Example 4 x Mo y S2 / SnS2, f) 1T content diagram.

[0030] Figure 7 a) SnS2 prepared in Example 1 of the present invention and b) SnS with different NaCl contents prepared in Examples 1 to 4 x Mo y IV diagram of S2 / SnS2.

[0031] Figure 8 In the figure, a) is the Raman image of SnO2 alone, and b) is the Raman image of SnO2 with NaCl added. DETAILED DESCRIPTION

[0032] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0034] Sn of the present invention x In the MoyS2 / SnS2 heterojunction, heterogeneous heteroatoms Sn are used for doping, and different masses of NaCl are adjusted to make SnO2 in SnO2 / MoO3 form tin oxychloride (SnO z Cl q ), promoting the generation of Sn x Mo y S2, thus obtaining Sn with different 1T ratios x Mo y S2 / SnS2, to reduce contact resistance and increase carrier mobility at the interface.

[0035] And the present invention prepares the above Sn x Mo y In the S2 / SnS2 heterojunction, the present invention uses tin disulfide nanosheets as a synthesis template. When it is known that the content of 1T phase is related to Sn atoms, an attempt is made to prepare SnO2 / MoO3 by adding SnCl4·5H2O and (NH4)6Mo7O 24 ·The ratio of 4H2O was changed from 0.15:1 to 0.1, 0.3, and 0.45:1. The inventors wanted to reduce and increase the content of Sn atoms, thereby reducing and increasing the 1T phase. However, the inventors found during the research process that simply changing the content of tin tetrachloride pentahydrate would not increase the content of 1T. This is because the melting point of MoO3 is about 795°C, and the melting point of SnO2 is about 1630°C. Under the condition that the hydrothermal temperature and time do not change, the Sn x Mo yThe growth of S2 will not be promoted, thereby failing to improve the sensitivity of the sensor and reduce the detection line.

[0036] In this regard, the present invention firstly converts SnO2 in SnO2 / MoO3 into tin oxychloride (SnO z Cl q ), the salt can reduce the melting point of the reactants and promote the formation of intermediates, thereby promoting the crystal growth of metal chalcogenides. And the general reaction of growth can be expressed as follows:

[0037]

[0038] Example 1

[0039] A Sn x Mo y The method for preparing a S2 / SnS2 heterojunction comprises the following steps:

[0040] (1) CS(NH2)2 and SnCl4·5H2O were dissolved in 19 mL of deionized water at a molar ratio of 15:1 to form a suspension. The suspension was then transferred to a reactor and the reaction conditions were set at 180°C for 12 h. The product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed three times with ethanol and deionized water alternately and dried at 80°C for 6 h to obtain SnS2 nanosheets.

[0041] (2) SnCl4·5H2O and (NH4)6Mo7O 24 4H2O was dissolved in 20mL of deionized water at a molar ratio of 0.15:1 to generate a suspension. Then, the suspension was transferred to a reactor and the reaction conditions were set at 220°C for 12 hours. The obtained product was centrifuged three times at 10000rpm for 10 minutes, and the sample was washed three times with ethanol and deionized water alternately. The SnO2 / MoO3 nanorod transition product was obtained by drying at 80°C for 6 hours.

[0042] (3) Sn x Mo yPreparation of S2 / SnS2: The SnS2 nanosheets prepared in step (1) were used as templates, mixed with SnO2 / MoO3 nanorods and CS(NH2)2 in a mass ratio of 5:1:33 to cause a sulfidation reaction, and then 66 mg of template PVP and 0.001 g of NaCl were added and dissolved in 20 mL of deionized water to generate a suspension. Then, the suspension was transferred to a reactor, and the reaction conditions were set to 220 ° C and the reaction time was 30 h. The obtained product was centrifuged three times at 10000 rpm for 10 min. The sample was washed alternately with ethanol and deionized water three times, and dried at 80 ° C for 6 h to obtain Sn x Mo y S2 / SnS2 heterojunction.

[0043] Example 2

[0044] A Sn x Mo y The method for preparing a S2 / SnS2 heterojunction comprises the following steps:

[0045] (1) CS(NH2)2 and SnCl4·5H2O were dissolved in 19 mL of deionized water at a molar ratio of 15:1 to form a suspension. The suspension was then transferred to a reactor and the reaction conditions were set at 180°C for 12 h. The product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed three times with ethanol and deionized water alternately and dried at 80°C for 6 h to obtain SnS2 nanosheets.

[0046] (2) SnCl4·5H2O and (NH4)6Mo7O 24 4H2O was dissolved in 20mL of deionized water at a molar ratio of 0.15:1 to generate a suspension. Then, the suspension was transferred to a reactor and the reaction conditions were set at 220°C for 12 hours. The obtained product was centrifuged three times at 10000rpm for 10 minutes, and the sample was washed three times with ethanol and deionized water alternately. The SnO2 / MoO3 nanorod transition product was obtained by drying at 80°C for 6 hours.

[0047] (3) Sn x Mo yPreparation of S2 / SnS2: The SnS2 nanosheets prepared in step (1) were used as templates, mixed with SnO2 / MoO3 nanorods and CS(NH2)2 in a mass ratio of 5:1:33, and a sulfidation reaction occurred. Then, 66 mg of the template PVP and 0.003 g of NaCl were dissolved in 20 mL of deionized water to generate a suspension. Then, the suspension was transferred to a reactor, and the reaction conditions were set to 220 ° C and the reaction time was 30 h. The obtained product was centrifuged three times at 10000 rpm for 10 min. The sample was washed alternately with ethanol and deionized water three times, and dried at 80 ° C for 6 h to obtain Sn x Mo y S2 / SnS2 heterojunction.

[0048] Example 3

[0049] A Sn x Mo y The method for preparing a S2 / SnS2 heterojunction comprises the following steps:

[0050] (1) CS(NH2)2 and SnCl4·5H2O were dissolved in 19 mL of deionized water at a molar ratio of 15:1 to form a suspension. The suspension was then transferred to a reactor and the reaction conditions were set at 180°C for 12 h. The product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed three times with ethanol and deionized water alternately and dried at 80°C for 6 h to obtain SnS2 nanosheets.

[0051] (2) SnCl4·5H2O and (NH4)6Mo7O 24 4H2O was dissolved in 20mL of deionized water at a molar ratio of 0.15:1 to generate a suspension. Then, the suspension was transferred to a reactor and the reaction conditions were set at 220°C for 12 hours. The obtained product was centrifuged three times at 10000rpm for 10 minutes, and the sample was washed three times with ethanol and deionized water alternately. The SnO2 / MoO3 nanorod transition product was obtained by drying at 80°C for 6 hours.

[0052] (3) Sn x Mo yPreparation of S2 / SnS2: The SnS2 nanosheets prepared in step (1) were used as templates, mixed with SnO2 / MoO3 nanorods and CS(NH2)2 in a mass ratio of 5:1:33, and a sulfidation reaction occurred. Then, 66 mg of template PVP and 0.006 g of NaCl were added and dissolved in 20 mL of deionized water to generate a suspension. Then, the suspension was transferred to a reactor, and the reaction conditions were set to 220 ° C and the reaction time was 30 h. The obtained product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed alternately with ethanol and deionized water three times, and dried at 80 ° C for 6 h to obtain Sn x Mo y S2 / SnS2 heterojunction.

[0053] Example 4

[0054] A Sn x Mo y The method for preparing a S2 / SnS2 heterojunction comprises the following steps:

[0055] (1) CS(NH2)2 and SnCl4·5H2O were dissolved in 19 mL of deionized water at a molar ratio of 15:1 to form a suspension. The suspension was then transferred to a reactor and the reaction conditions were set at 180°C for 12 h. The product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed three times with ethanol and deionized water alternately and dried at 80°C for 6 h to obtain SnS2 nanosheets.

[0056] (2) SnCl4·5H2O and (NH4)6Mo7O 24 4H2O was dissolved in 20mL of deionized water at a molar ratio of 0.15:1 to generate a suspension. Then, the suspension was transferred to a reactor and the reaction conditions were set at 220°C for 12 hours. The obtained product was centrifuged three times at 10000rpm for 10 minutes, and the sample was washed three times with ethanol and deionized water alternately. The SnO2 / MoO3 nanorod transition product was obtained by drying at 80°C for 6 hours.

[0057] (3) Sn x Mo yPreparation of S2 / SnS2: The SnS2 nanosheets prepared in step (1) were used as templates, mixed with SnO2 / MoO3 nanorods and CS(NH2)2 in a mass ratio of 5:1:33, and a sulfidation reaction occurred. Then, 66 mg of the template PVP and 0.009 g of NaCl were dissolved in 20 mL of deionized water to generate a suspension. Then, the suspension was transferred to a reactor, and the reaction conditions were set to 220 ° C and the reaction time was 30 h. The obtained product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed alternately with ethanol and deionized water three times, and dried at 80 ° C for 6 h to obtain Sn x Mo y S2 / SnS2 heterojunction.

[0058] Example 5

[0059] A Sn x Mo y The method for preparing a S2 / SnS2 heterojunction comprises the following steps:

[0060] (1) CS(NH2)2 and SnCl4·5H2O were dissolved in 19 mL of deionized water at a molar ratio of 15:1 to form a suspension. The suspension was then transferred to a reactor and the reaction conditions were set at 120°C for 12 h. The product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed three times with ethanol and deionized water alternately and dried at 80°C for 6 h to obtain SnS2 nanosheets.

[0061] (2) SnCl4·5H2O and (NH4)6Mo7O 24 4H2O was dissolved in 20mL of deionized water at a ratio of 0.1:1 to generate a suspension. Then, the suspension was transferred to a reactor and the reaction conditions were set at 200°C for 10 hours. The obtained product was centrifuged three times at 10000rpm for 10 minutes, and the sample was washed three times with ethanol and deionized water alternately. The SnO2 / MoO3 nanorod transition product was obtained by drying at 80°C for 6 hours.

[0062] (3) Sn x Mo yPreparation of S2 / SnS2: The SnS2 nanosheets prepared in step (1) were used as templates, mixed with SnO2 / MoO3 nanorods and CS(NH2)2 in a mass ratio of 5:1:33, and a sulfidation reaction occurred. Then, 66 mg PVP and 0.009 g NaCl were added and dissolved in 20 mL deionized water to generate a suspension. Then, the suspension was transferred to a reactor, and the reaction conditions were set to 180 ° C and the reaction time was 29 h. The obtained product was centrifuged three times at 10000 rpm for 10 min. The sample was washed alternately with ethanol and deionized water three times, and dried at 80 ° C for 6 h to obtain Sn x Mo y S2 / SnS2 heterojunction.

[0063] Example 6

[0064] A Sn x Mo y The method for preparing a S2 / SnS2 heterojunction comprises the following steps:

[0065] (1) CS(NH2)2 and SnCl4·5H2O were dissolved in 20 mL of deionized water at a molar ratio of 15:1 to form a suspension. The suspension was then transferred to a reactor and the reaction conditions were set at 160°C for 10 h. The product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed three times with ethanol and deionized water alternately and dried at 80°C for 6 h to obtain SnS2 nanosheets.

[0066] (2) SnCl4·5H2O and (NH4)6Mo7O 24 4H2O was dissolved in 19mL deionized water at a molar ratio of 0.45:1 to generate a suspension. Then, the suspension was transferred to a reactor and the reaction conditions were set at 180°C for 12 hours. The obtained product was centrifuged three times at 10000rpm for 10 minutes, and the sample was washed three times with ethanol and deionized water alternately. The SnO2 / MoO3 nanorod transition product was obtained by drying at 80°C for 6 hours.

[0067] (3) Sn x Mo yPreparation of S2 / SnS2: The SnS2 nanosheets prepared in step (1) were used as templates, mixed with SnO2 / MoO3 nanorods and CS(NH2)2 in a mass ratio of 5:1:33, and a sulfidation reaction occurred. Then, 66 mg of the template PVP and 0.009 g of NaCl were dissolved in 20 mL of deionized water to generate a suspension. Then, the suspension was transferred to a reactor, and the reaction conditions were set to 200 ° C and the reaction time was 29 h. The obtained product was centrifuged three times at 10,000 rpm for 10 min. The sample was washed alternately with ethanol and deionized water three times, and dried at 80 ° C for 6 h to obtain Sn x Mo y S2 / SnS2 heterojunction.

[0068] Results Analysis

[0069] Figure 1 a) SEM and b) XRD images of SnO2 / MoO3 nanorods prepared in Example 1 of the present invention. The nanorod structure can be seen from the SEM image, and the XRD results show that SnO2 / MoO3 nanorods are successfully synthesized.

[0070] Figure 2 SnS2 prepared in Examples 1 to 4 of the present invention and Sn with different NaCl contents x Mo y SEM images of S2 / SnS2; a) SnS2; b) Sn x Mo y S2 / SnS2; c) Sn prepared in Example 1 x Mo y S2 / SnS2; d) SSn prepared in Example 2 x Mo y S2 / SnS2; e) Sn prepared in Example 3 x MoyS2 / SnS2; f) Sn prepared in Example 4 x Mo y S2 / SnS2. It can be seen from the figure that SnS2 has a hexagonal morphology. x Mo y There is something covering the SEM of S2 / SnS2.

[0071] Figure 3 Prepare Sn with NaCl content of 0.001g for Example 1 of the present invention x Mo y a) TEM of S2 / SnS2; b) high-resolution image. It can be seen from the figure that the hexagonal morphology of SnS2 is covered with something and has good crystallinity. By comparing with the standard card, the lattice spacing is determined to be Sn x Moy S2, the results show that the hexagonal template generates Sn x Mo y S2.

[0072] Figure 4 This is the XRD diagram of SnS2 prepared in Example 1 of the present invention. It can be seen from the figure that the prepared SnS2 sample is the same as the standard card, and the results show that tin disulfide is synthesized.

[0073] Figure 5 Sn with different NaCl contents prepared in Examples 1 to 4 of the present invention x Mo y XRD diagram of S2 / SnS2, b) Sn prepared in Example 1 x Mo y Raman graph of S2 / SnS2. From the XRD graph, it can be seen that SnS2 is not visible in the prepared sample, so for Sn x Mo y S2 / SnS2 (NaCl 0.001g) was subjected to Raman testing, and the results showed the presence of molybdenum disulfide and tin disulfide.

[0074] Figure 6 Sn with different NaCl contents prepared in Examples 1 to 4 of the present invention x Mo y XPS graph of molybdenum element and corresponding 1T content of S2 / SnS2; a) Sn x Mo y S2 / SnS2; b) Sn prepared in Example 1 x Mo y S2 / SnS2 (NaCl 0.001 g); c) Sn prepared in Example 2 x Mo y S2 / SnS2 (NaCl 0.003 g); d) Sn prepared in Example 3 x Mo y S2 / SnS2 (NaCl 0.006 g); e) Sn prepared in Example 4 x Mo y S2 / SnS2 (NaCl 0.009 g), f) 1T content diagram. It can be seen from the figure that 1T / 2H exists and increases with the increase of salt. The results show that salt has a promoting effect on 1T phase.

[0075] Figure 7 a) SnS2 prepared in Example 1 of the present invention and b) SnS with different NaCl contents prepared in Examples 1 to 4 x Mo yIV diagram of S2 / SnS2. It can be seen from the figure that as the NaCl content increases, the corresponding current increases, and the results show that the 1T content increases with the increase of salt.

[0076] Figure 8 In the figure, a) is the Raman image of SnO2 alone, and b) is the Raman image of adding NaCl to SnO2. It can be seen from the figure that when NaCl is added, the Raman peak of SnO2 increases. The results show that the increased peak should belong to the transition product tin oxychloride SnO z Cl q .

[0077] In summary, the present invention uses molybdate and tetravalent tin salt as raw materials, obtains SnO2 / MoO3 nanorod transition product through hydrothermal synthesis, then uses SnS2 nanosheets as templates, mixes with SnO2 / MoO3 nanorod transition product and CS(NH2)2 for sulfurization reaction to obtain a mixed solution, adds polyvinyl pyrrolidone template and NaCl to the mixed solution to generate a suspension, and finally performs a hydrothermal reaction on the suspension, wherein NaCl causes SnO2 in SnO2 / MoO3 to form tin oxide chloride, which then reacts with MoO3 in SnO2 / MoO3 and S in SnS2 nanosheets to obtain Sn x Mo y S2 / SnS2 heterojunction, Sn x Mo y The heterogeneous heteroatom Sn is used for doping in the S2 / SnS2 heterojunction, and the SnO2 in SnO2 / MoO3 is formed into tin oxychloride SnO by adjusting the addition ratio of NaCl. z Cl q , the salt can reduce the melting point of the reactants and promote the formation of intermediates, thereby promoting the metal chalcogenide Sn x Mo y The crystal formation of S2 causes the transformation of 2H-MoS2 to 1T-MoS2, thus obtaining Sn with different 1T ratios. x Mo y S2 / SnS2, achieving low contact resistance and improving carrier mobility at the interface.

[0078] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0079] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A 1T Sn with adjustable metal phase ratio x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The following steps are involved: Using molybdate and tetravalent tin salt as raw materials and water as solvent, SnO2 / MoO3 nanorod transition products were obtained through hydrothermal synthesis. SnS2 nanosheets are used as templates, mixed with SnO2 / MoO3 nanorod transition products and CS(NH2)2 for sulfurization reaction to obtain a mixed solution, polyvinyl pyrrolidone template and NaCl are added to the mixed solution to generate a suspension, and the suspension is subjected to a hydrothermal reaction. During the hydrothermal reaction, NaCl causes SnO2 in SnO2 / MoO3 to form tin oxide chloride, which then reacts with MoO3 in SnO2 / MoO3 and S in SnS2 nanosheets to transform 2H-MoS2 into 1T-MoS2. By adjusting the amount of NaCl added, Sn with different 1T metal phase ratios can be obtained. x Mo y S2 / SnS2 heterojunction.

2. The Sn with adjustable 1T metal phase ratio according to claim 1 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The molar ratio of NaCl to tetravalent tin salt is 0.5-1.5:

1.

3. The Sn with adjustable 1T metal phase ratio according to claim 1 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The molar ratio of molybdate to tetravalent tin salt is 1:0.1-0.45, and the dosage ratio of tetravalent tin salt to water is 0.1 mol-0.45 mol:19 mL-20 mL.

4. The Sn with adjustable 1T metal phase ratio according to claim 1 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The mass ratio of SnS2 nanosheets to SnO2 / MoO3 nanorods is 5:0.5-1, and the mass ratio of SnO2 / MoO3 nanorod transition product to CS(NH2)2 is 1:30-33.

5. The Sn with adjustable 1T metal phase ratio according to claim 1 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The hydrothermal reaction temperature for preparing SnO2 / MoO3 nanorod transition products is 180°C to 220°C, and the hydrothermal reaction time is 10h to 12h.

6. The Sn with adjustable 1T metal phase ratio according to claim 1 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: Preparation of Sn x Mo y In the case of S2 / SnS2 heterojunction, the hydrothermal reaction temperature is 180°C to 220°C, and the hydrothermal reaction time is 28h to 30h.

7. The Sn with adjustable 1T metal phase ratio according to claim 1 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The molybdate is ammonium molybdate or sodium molybdate dihydrate.

8. The Sn with adjustable 1T metal phase ratio according to claim 1 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The SnS2 nanosheets are prepared by the following steps: Using thiourea as a sulfur source and tetravalent tin salt as a tin source and water as a solvent, a hydrothermal reaction is carried out at 160°C to 260°C for 10h to 12h to obtain SnS2 nanosheets.

9. The Sn with adjustable 1T metal phase ratio according to claim 8 x Mo y The method for preparing a S2 / SnS2 heterojunction is characterized in that: The usage ratio of thiourea, tetravalent tin salt and water is 15 mol: 1 mol: 19 mL to 20 mL.

10. A Sn with adjustable 1T metal phase ratio obtained by the preparation method according to any one of claims 1 to 9 x Mo y S2 / SnS2 heterojunction.